Selective Extraction of Sinapic Acid Derivatives from Mustard Seed Meal by Acting on pH: Toward a High Antioxidant Activity Rich Extract - Morad Chadni; Amandine L. Flourat; Valentin Reungoat; Louis M. M. Mouterde; Florent Allais; Irina Ioannou (Molecules, 2021)
The aim of this paper is to study the effect of the pH on the extraction of sinapic acid and its derivatives from mustard seed meal. Solutions of acidic pH (pH 2), basic pH (pH 12) and distilled water (uncontrolled pH ~ 4.5) were tested at different percentages of ethanol. The maximum extraction yield for sinapic acid (13.22 µmol/g of dry matter (DM)) was obtained with a buffered aqueous solution at pH 12. For ethyl sinapate, the maximum extraction yield reached 9.81 µmol/g DM with 70% ethanol/buffered aqueous solution at pH 12. The maximum extraction yield of sinapine (15.73 µmol/g DM) was achieved with 70% ethanol/buffered aqueous solution at pH 2. The antioxidant activity of each extract was assessed by DPPH assay; the results indicated that the extracts obtained at pH 12 and at low ethanol percentages (<50%) exhibit a higher antioxidant activity than extracts obtained at acidic conditions. Maximum antioxidant activity was reached at pH 12 with buffer solution (11.37 mg of Trolox Equivalent/g DM), which confirms that sinapic acid-rich fractions exhibit a higher antioxidant activity. Thus, to obtain rich antioxidant extracts, it is suggested to promote the presence of sinapic acid in the extracts.